SEXUAL RECESSION IN URBAN MUSLIM SOCIETIES: A REVIEW OF MAQASHID SHARIA AND ITS IMPLICATIONS - Imaro Sidqi; Mhd. Rasidin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2023)
Sex recession is increasing from year to year in various countries. This phenomenon has the opportunity and potential to have a negative impact on the future of the younger generation and even the world’s population because it causes harm to many aspects, such as economic, political, socio-cultural, and religious aspects. This article aims to describe the law of sex recession from the viewpoint of Islamic marriage law and seeks to formulate the concept of policies to minimize sex recession in the world, especially in Indonesia, through maqashid sharia as the basis for its formation. The research method used is juridical-normative with a philosophical and conceptual approach. The theory used is maqashid sharia. The results of this research show that the sexual recession threatens the life of the nation and state. This is proven by the many impacts experienced by many countries, both from an economic, socio-cultural, political, and religious perspective. So, countries are flocking to make policies to reduce the sex recession. The authors offer policy concepts that can be considered, such as strengthening pre-marital education, increasing family resilience, efforts to minimize divorce, and building awareness in the Muslim community regarding marriage law, where these policies are conceptualized based on maqashid sharia. Policies that have clear direction can minimize the sexual recession effectively and efficiently in people’s lives.